Kemerdekaan Pendididikan Anak Pedalaman (Analisis Semiotika Tentang Pendidikan Yang Membebaskan Dalam Film Sokola Rimba (2013) - Nissa, Intan Adillia; Masrukin; Arizal Mutahir (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2024)
This research is based on the fact that education in Indonesia is not distributed evenly, especially in areas that fall into the 3 category (Outermost, Remote and Disadvantaged). The community does not yet have adequate access and facilities to carry out teaching and learning activities. The aim of this research is to understand and explain the semiotic analysis of liberating education in the film Sokola Rimba (2013). The author uses qualitative research methods and semiotic analysis according to the Charles Sanders Pierce model. This semiotic model focuses on icons, indices and symbols that appear in the film Sokola Rimba. The findings from this research are that the interpretation of dialogue text, images and videos from the film is able to depict a social reality. This social reality is a picture of educational inequality and the struggle of the figures to gain educational independence. It is hoped that this article can help the government to be more responsive in solving problems surrounding educational independence in rural communities.